ANALISA KALIBRASI ALAT INFANT WARMER MENGGUNAKAN ALAT INCUBATOR ANALYZER - M. Suganda Malau; Yulizham Yulizham (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
Infant warmer is one of the electromedical devices used to provide comfort and warmth to newborns, where the baby needs a temperature that is in accordance with the temperature in the mother's womb, which is between 34oC – 37oC. The purpose of this research is to study the Calibration technique and the calculation of the uncertainty of temperature measurement data.The results obtained from the calibration and calculations are ± 0,54oC for temperature. From these results, it was stated that the infant warmer was declared fit for use. As a rule, the test pass threshold value is ± 2 oC for temperature.